Needs Analysis of Project-Based Learning Integrated with Local Wisdom to Enhance Literacy in Elementary Schools - Rusidah Rusidah; Santi Oktarina; Farida Ratu Wargadalem (AL-ISHLAH: Jurnal Pendidikan, 2025)
Literacy in elementary education involves not only reading and writing but also critical, creative, and contextual thinking. However, students often face difficulties in writing due to limited exposure to contextualized learning models and culturally relevant materials. This study explores the need for a Project-Based Learning (PjBL) model integrated with local wisdom to enhance students’ writing literacy, particularly in composing folklore. This paper reports on the initial analysis phase of a broader model development effort using the ADDIE framework. A mixed-methods approach was employed, involving 61 fourth-grade students and 3 teachers from SD Negeri Air Balui. Data were gathered through validated questionnaires and semi-structured interviews and analyzed descriptively. The findings indicate a strong need for a culturally contextual PjBL model. Over 85% of students and 75% of teachers expressed that such a model would significantly support literacy development, particularly in writing. Students also identified difficulties in idea generation and writing processes, largely due to limited instructional support and media. Integrating local wisdom into PjBL is seen as an effective strategy to enhance literacy, foster cultural appreciation, and build essential 21st-century skills. The study emphasizes the importance of developing a contextual, collaborative, and meaningful learning model to support both academic and character development in elementary education.